Theory-based assessment, treatment, and prevention of sexual aggression - Hall, Gordon C. Nagayama (Oxford University Press, 1996)
Sexual aggression is a pervasive societal problem in that approximately one in four adults have been either victims or perpetrators of sexually aggressive behaviour. In this book, suggestions are offered for effective assessment and treatment of sexual aggressions based on state-of-the-science theory and research. Hall and Hirschman's Quadripartite Model Sexual Aggression, which suggests that physiological sexual arousal, cognitive distortions, and developmentally related personality problems as motivational variables for sexually aggressive behaviour, provides the unifying theoretical framework for the book. Clinical approaches relevant for sexually aggressive behaviour both against adults and against children are discussed. This book breaks new ground by proposing preventive interventions with potential perpetrators of sexual aggression.